CAND1 is required for pollen viability in Arabidopsis thaliana—a test of the adaptive exchange hypothesis - Li, Lihong; Garsamo, Melaku; Yuan, Jing; Wang, Xiaojin; Lam, Susan H.; Varala, Kranthi; Boavida, Leonor C.; Zhou, Yun; Liu, Xing (Frontiers in Plant Science, 2022)
The dynamic assembly of SKP1•CUL1•F-box protein (SCF) ubiquitin ligases is important for protein ubiquitination and degradation. This process is enabled by CAND1, which exchanges F-box proteins associated with the common CUL1 scaffold, and thereby, recycles the limited CUL1 core and allows diverse F-box proteins to assemble active SCFs. Previous human cell biological and computational studies have led to the adaptive exchange hypothesis, which suggests that the CAND1-mediated exchange confers plasticity on the SCF system, allowing cells to tolerate large variations in F-box protein expression. Here, we tested this hypothesis using Arabidopsis thaliana, a multicellular organism expressing hundreds of F-box protein genes at variable levels in different tissues. The cand1 null mutant in Arabidopsis is viable but produce almost no seeds. Bioinformatic, cell biological, and developmental analyses revealed that the low fertility in the cand1 mutant is associated with cell death in pollen, where the net expression of F-box protein genes is significantly higher than any other Arabidopsis tissue. In addition, we show that the transmission efficiency of the cand1 null allele was reduced through the male but not the female gametophyte. Our results suggest that CAND1 activity is essential in cells or tissues expressing high levels of F-box proteins. This finding is consistent with the proposed adaptive exchange hypothesis, demonstrating the necessity of the evolutionarily conserved CAND1-mediated exchange system in the development of a multicellular organism.